Pengaruh Integrasi Pendidikan Karakter Dalam Pembelajaran Kimia Terhadap Kepedulian Lingkungan Peserta Didik - Fitria Rizkiana; Herlina Apriani; Novi Rahmawanti (FKIP University of Mataram, 2026)
This study aims to determine the effect of integrating character education into chemistry learning on students’ environmental awareness at SMA Negeri 12 Banjarmasin. The research employed a quasi-experimental design using the posttest-only control group design. The sample consisted of two classes: an experimental class that received chemistry learning integrated with environmental care values through a contextual discussion approach, and a control class that received conventional instruction. Data were collected using an environmental awareness questionnaire and analyzed using descriptive and inferential statistics with the aid of JAMOVI 2.6.44 software. The results showed no significant difference between the environmental awareness scores of students in the experimental and control classes (p = 0.687 > 0.05), with an effect size of -0.103, indicating a very small influence. These findings suggest that the integration of character education into chemistry learning did not significantly improve students’ environmental awareness. However, this approach has the potential to serve as an initial step in fostering environmental consciousness when implemented consistently and contextually.